Optimal Physicochemical Properties of Antibody–Nanoparticle Conjugates for Improved Tumor Targeting. Issue 24 (15th March 2022) - Mittelheisser, Vincent; Coliat, Pierre; Moeglin, Eric; Goepp, Lilian; Goetz, Jacky G.; Charbonnière, Loic J.; Pivot, Xavier; Detappe, Alexandre
Abstract: Tumor‐targeted antibody (mAb)/fragment‐conjugated nanoparticles (NPs) represent an innovative strategy for improving the local delivery of small molecules. However, the physicochemical properties of full mAb–NPs and fragment–NPs—that is, NP material, size, charge, as well as the targeting antibody moiety, and the linker conjugation strategies—remain to be optimized to achieve an efficient tumor targeting. A meta‐analysis of 161 peer‐reviewed studies is presented, which describes the use of tumor‐targeted mAb–NPs and fragment−NPs from 2009 to 2021. The use of these targeted NPs is confirmed to result in significantly greater tumor uptake of NPs than that of naked NPs (7.9 ± 1.9% ID g −1 versus 3.2 ± 0.6% ID g −1, respectively). The study further demonstrates that for lipidic NPs, fragment–NPs provide a significantly higher tumor uptake than full mAb–NPs. In parallel, for both polymeric and organic/inorganic NPs, full mAb–NPs yield a significant higher tumor uptake than fragment–NPs. In addition, for both lipidic and polymeric NPs, the tumor uptake is improved with the smallest sizes of the conjugates. Finally, the pharmacokinetics of the conjugates are demonstrated to be driven by the NPs and not by the antibody moieties, independently of using full mAb–NPs or fragment–NPs, confirming the importance of optimizing the NP design to improve the tumor uptake. Abstract : Tumor‐targeted nanoparticles represent an innovative strategy for improving the local delivery of small molecules. This meta‐analysis describes the biodistribution and pharmacokinetic profiles of antibody‐/fragment‐targeted nanoparticles. The impact of the physicochemical properties of the nanoparticles and the optimal conjugation strategy to optimize the tumor targeting efficiencies is discussed.